Blended Learning: the transformation of Higher Education Curriculum - Vasileiou, Ismini (Ανοικτή Εκπαίδευση: το περιοδικό για την Ανοικτή και εξ Αποστάσεως Εκπαίδευση και την Εκπαιδευτική Τεχνολογία, 2009)
This paper is a review of literature and current information related to blended learning. It will deal with several primary research issues which will include the redefining of the role of student, the role of teacher/tutor, learning and the educational establishment. The paper will analyse and discuss the selection of strategies to increase interactivity and active learning, learner characteristics, learner support and operational issues.